Tun Sri Lanang fī Masār al-Tārīkh wa ‘Alāqatuhu bi Intishār al-Islām fī Aceh - Madjid, M. Dien (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2012)
This article discusses the role of Tun Sri Lanang in designing the socio-political and religious life and in introducing both the structural and cultural changes in the Aceh Darussalam Kingdom. This article focuses on the period of Sultan Iskandar Muda until Ratu Safiatuddin. In addition to his popularity as adviser of Sultan Iskandar Muda, Tun Sri Lanang was also well-known as a pioneer in spreading Islam in east Aceh especially in Samalanga. Although he had no strong knowledge on Islam, Tun Sri Lanang had a strong interest in the existence of Islam in Aceh. The fact that Aceh in his time was noted as a centre of Islamic civilization in Southeast Asia could not be separated from the role of hulubalang and other kingdom officials who had strong interests in disseminating Islam and developing knowledge.DOI: 10.15408/sdi.v19i1.371